2019
DOI: 10.1080/09658211.2018.1563615
|View full text |Cite
|
Sign up to set email alerts
|

Do children use different forms of verbal rehearsal in serial picture recall tasks? A multi-method study

Abstract: Do children use different forms of verbal rehearsal in serial picture recall tasks? A multi-method study Use of verbal rehearsal is a key issue in memory development. However, we still lack detailed and triangulated information about the early development and the circumstances in which different forms of rehearsal are used. To further understand significant factors that affect children's use of various forms of rehearsal, the present study involving 108 primary school children adopted a multi-method approach. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 33 publications
(48 reference statements)
1
15
0
Order By: Relevance
“…Researchers have attempted to measure all three forms of rehearsal indirectly through response times -either the times for self-paced encoding of further elements of the memory list (Morey et al, 2018;Poloczek, Henry, Messer, & Büttner, 2019) or the response times to a distractor task during the retention interval (Naveh-Benjamin & Jonides, 1984;Thalmann et al, 2019;Vergauwe, Camos, & Barrouillet, 2014). The underlying assumptions are that rehearsal takes time, and therefore participants postpone other processes until they finished rehearsing, and that they take more time to rehearse longer memory lists.…”
Section: Box 3: How To Measure Rehearsalmentioning
confidence: 99%
“…Researchers have attempted to measure all three forms of rehearsal indirectly through response times -either the times for self-paced encoding of further elements of the memory list (Morey et al, 2018;Poloczek, Henry, Messer, & Büttner, 2019) or the response times to a distractor task during the retention interval (Naveh-Benjamin & Jonides, 1984;Thalmann et al, 2019;Vergauwe, Camos, & Barrouillet, 2014). The underlying assumptions are that rehearsal takes time, and therefore participants postpone other processes until they finished rehearsing, and that they take more time to rehearse longer memory lists.…”
Section: Box 3: How To Measure Rehearsalmentioning
confidence: 99%
“…To further investigate this hypothesis, we manipulated a dimension of language that has not been associated with analogical reasoning in children (i.e., the use of phonological recoding). Phonological recoding is associated with the articulatory or sub-vocal rehearsal process in Baddeley's model of working memory and refers to the process by which written and visual material can be recoded into a phonological form that can be registered and maintained in the phonological store (Baddeley, 1992;Emerson & Miyake, 2003;Norris, Butterfield, Hall, & Page, 2018;Poloczek, Henry, Messer, & Büttner, 2019). This relies on covert articulation and on phonological representations (Baddeley, Thomson, & Buchanan, 1975;Balthazar, 2003;Norris et al, 2018;Poloczek et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Because the increasing differences that we found in our study developed between grade 4 and grade 5, differences in the automatization of subvocal rehearsal that, according to Fischbach et al (2014), occur during this age might explain the results. Also of interest is a study conducted by Poloczek, Henry, Messer, and Büttner (2019), which showed that at approximately 10 years of age, cumulative rehearsal (as opposed to single naming) increasingly emerges as a memory strategy to boost memory performance further. More importantly, the authors revealed that high‐performing 10‐year‐old students used cumulative rehearsal to improve immediate memory more often and more efficiently than their low‐performing peers.…”
Section: Discussionmentioning
confidence: 99%